Experimental study on in-situ simulation of rainfall-induced soil erosion in forest lands converted to cash crop areas in Dabie Mountains. - Gao Li; Tao Yang; Rui Chen; Haogang Dong; Feng Wu; Qinghua Zhan; Jinyan Huang; Minxuan Luo; Li Wang (PLoS ONE)
Soil erosion is a pervasive global challenge and a significant ecological and environmental concern in China. Its occurrence frequently triggers ecological crises, including soil degradation and water contamination. It is of great scientific and practical significance to study the factors influencing the mechanism of soil erosion occurrence. Economic development in the Dabie Mountains of China has necessitated the conversion of vast tracts of forest land into economic crops, notably tea gardens and orchards, thereby disrupting soil structure and precipitating large-scale soil erosion. Rainfall serves as the primary catalyst for soil erosion in this region. Therefore, this study was designed to reveal the evolution characteristics of rainfall-induced slope erosion and the key influencing factors in the forest land converted to cash crop area in Dabie Mountains. It focused on a tea plantation slope of the Dabie Mountains, employing four rainfall scenarios, i.e. light rain, moderate rain, heavy rain, and heavy rain following drought, to conduct in-situ simulation experiments, mirroring the prevalent rainfall patterns in the study region. Monitoring stations for soil moisture content, slope runoff, and soil erosion were strategically positioned at varying depths across experimental plots with vegetation cover percentages of 20%, 40%, and 60%. Mathematical methods of descriptive statistics were used to analyze the monitored runoff, soil erosion and soil water content data, and to study the characteristics of their changes and response relationships. The findings underscore that rainfall prompts a swift surge in surface soil moisture, destabilizing the soil surface and culminating in slope erosion; thus, the rate of change in surface soil moisture content emerges as a pivotal indicator for predicting slope soil erosion. Furthermore, within the bounds of rainfall infiltration, preceding drought conditions followed by intense rainfall exacerbate soil erosion accumulation, highlighting the significance of initial soil moisture content as a critical factor. Lastly, for the economic crop cultivation zones in the Dabie Mountains, achieving a vegetation cover of 40% or more can significantly enhance soil water retention capacity and the overall soil and water conservation efficacy.